Telling new tales in new spaces: La fiaba in America - Reza, M (University of Toronto Press, 2017)
Using a corpus drawn from published and archival material in Italy and the United States, this article focuses on the movement of fairy and folk tales from Italian communities across the Atlantic to the United States during the twentieth century. I firstly discuss the change in the space in which stories are told together with the role of the storyteller, comparing accounts from Italy and the USA, the frequency with which teller and audience interact, and the manner in which these dynamics change. Secondly, I look at personal experience narratives as examples of changes in the type of story recalled, but also as a means to show an overlap between traditional tales and the lived experiences of Italian migrants.